EVALUASI PENGENDALIAN INTERN PADA SIKLUS PENGGAJIAN PT ANEKALOKA INDOTUNA DI BITUNG - Marau, Maria Marisa; Nangoi, Grace B.; Manossoh, Hendrik (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
A company is considered successful if it can manage their payroll cycles. This is because the payroll can directly affect the performance of the employee. Companies must ensure the welfare of workers by giving them rights that salary in return for services rendered to the company's employees. Each activity requires a control of our lives to what is being and has been done. It is therefore necessary internal controls over payroll cycle at a company in terms of oversight of payroll. This study was conducted to determine and evaluate the Internal Control of Payroll Cyele in PT.Anekaloka Indotuna. The object of this research is PT.Anekaloka Indotuna Bitung, the company is engaged in the field of shipping and fisheries. The research method is qualitative method. The results showed that the internal control PT.Anekaloka payroll cycle has not completely efficient. Head of the company should increase the discipline monitor activity of employees. Keywords : evaluation, payroll, internal control